STATE POLICY ON THE DEVELOPMENT OF TOURISM IN UZBEKISTAN - Ergasheva, Mahliyo; S.B.Shadmanova (Social science and innovation, 2024)
It is clear that the rich ancient history of our country, our holy places, comfortable and beautiful natural environment attract not only our compatriots, but also tourists from all over the world. The head of our state gave instructions to officials to organize tourism clusters connecting hotel, culture, nature, ethnic and gastronomic centers, to introduce the "hospitable environment certificate for tourists". implementation of international norms and standards aimed at creating favorable conditions for the development of transport logistics, expansion of internal and external routes, and improvement of the quality of transport services.